2019
DOI: 10.1371/journal.pone.0223602
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels after childbirth and association with number of children: A population-based cohort study

Abstract: ObjectiveLow parity women are at increased risk of cardiovascular mortality. Unfavourable lipid profiles have been found in one-child mothers years before they conceive. However, it remains unclear whether unfavourable lipid profiles are evident in these women also after their first birth. The aim was to estimate post-pregnancy lipid levels in one-child mothers compared to mothers with two or more children and to assess these lipid’s associations with number of children.MethodsWe used data on 32 618 parous wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…El Khoudary SR et al has found that postmenopausal women's decreased estrogen levels are believed to contribute to the rise in CVD in postmenopausal women [7]. Previous studies have shown that in addition to estrogen levels, CVD may also be influenced by other reproductive factors, including parity, lipid levels after childbirth, and miscarriage or recurrent miscarriage [8][9][10][11]. Bridger Staatz C et al also found that a variety of family factors, including the number of children, the age at first birth (AFB) and age of last birth (ALB), and the birth interval have been connected obesity and overweight [12].…”
Section: Introductionmentioning
confidence: 99%
“…El Khoudary SR et al has found that postmenopausal women's decreased estrogen levels are believed to contribute to the rise in CVD in postmenopausal women [7]. Previous studies have shown that in addition to estrogen levels, CVD may also be influenced by other reproductive factors, including parity, lipid levels after childbirth, and miscarriage or recurrent miscarriage [8][9][10][11]. Bridger Staatz C et al also found that a variety of family factors, including the number of children, the age at first birth (AFB) and age of last birth (ALB), and the birth interval have been connected obesity and overweight [12].…”
Section: Introductionmentioning
confidence: 99%